Towards Understanding the Reactivity and Optical Properties of Organosilicon Sulfide Clusters. (15th December 2020) - Hanau, Katharina; Schwan, Sebastian; Schäfer, Moritz R.; Müller, Marius J.; Dues, Christof; Rinn, Niklas; Sanna, Simone; Chatterjee, Sangam; Mollenhauer, Doreen; Dehnen, Stefanie
Abstract: We report the extension of the class of organotetrel sulfide clusters with further examples of the still rare silicon‐based species, synthesized from RSiCl3 with R=phenyl (Ph, I ), naphthyl (Np, II ), and styryl (Sty, III ) with Na2 S. Besides known [(PhSi)4 S6 ] (IV ), new compounds [(NpSi)4 S6 ] (1 ) and [(StySi)4 S6 ] (2 ) were obtained, the first two of which underwent reactions with [AuCl(PPh3 )] to form ternary complexes. DFT studies of cluster dimers helped us understand the differences between the habit of Si4 S6 ‐ and Sn4 S6 ‐based compounds. Crystalline 1 showed a pronounced nonlinear optical response, while for intrinsically amorphous 2, the chemical damage threshold seems to inhibit a corresponding observation. Calculations within the independent particle approximation served to rationalize and compare electronic and optical excitations of [(RSi)4 S6 ] clusters (R=Ph, Np). The calculations reproduced the measured data and allowed for the interpretation of the main spectroscopic features. Abstract : To gain insight into the nonlinear optical properties and reactivity of organotetrel chalcogenide clusters, we studied the silicon homologues, [(RSi)4 S6 ] (R=Ph, Np, Sty), and their products upon reaction with [AuCl(PPh3 )], [{RSi(μ‐S)}2 {AuPPh3 (μ‐S)}2 ]. Quantum chemical studies of cluster dimers elucidated the differences in the habit of silicon and tin compounds, and DFT calculations of crystalline models confirmed the applicability of these methods.